One-Step Preparation of Z-Isomer-Rich β-Carotene Nanosuspensions Utilizing a Natural Catalyst, Allyl Isothiocyanate, via Supercritical CO2 - Yelin Zhang (Symmetry, 2020)
This study aims to improve the production efficiency of β-carotene suspensions using a naturally occurring Z-isomerization-accelerating catalyst, allyl isothiocyanate (AITC), via supercritical CO2 (SC-CO2). Namely, utilizing solubility improvement of β-carotene with the Z-isomerization by adding AITC in the SC-CO2-used dispersion process, the encapsulation efficiency of β-carotene was enhanced. The dispersion of β-carotene was conducted by ultrasonic treatment, and there was no involvement of organic solvents in the whole process. When 100 mg of AITC was added in the dispersion process, the encapsulation efficiency (β-carotene content in resulting suspension) was approximately 3.5 times higher than that without addition of the catalyst. Moreover, the Z-isomer ratio of β-carotene in the suspensions significantly improved, that is, it was approximately 12 times higher than the raw β-carotene material. Since Z-isomers of β-carotene are known to have higher antiatherosclerotic and antiatherogenic activities compared to the all-E-isomer, this one-step method not only efficiently produces β-carotene suspensions without organic solvents but also enhances the bioactivities of them.